Integrating the Engineering Design Process into STEM-Based Physics Education: A Systematic Literature Review of Research Trends, Implementation, and Effectiveness - Putri Flamonia; Lilik Hasanah; Winny Liliawati; Irma Rahma Suwarma (Jurnal Penelitian Pendidikan IPA, 2026)
Research on integrating the Engineering Design Process (EDP) into STEM-based physics education has expanded, but prior reviews have generally examined STEM or EDP broadly, while a recent physics-focused review primarily synthesized learning impacts. An integrated map linking publication trends, implementation contexts, student-designed products, outcome measures, and evidence of effectiveness remains limited. This systematic literature review addresses that gap by analyzing peer-reviewed studies published from 2021 to 2026. Following PRISMA 2020, searches of Scopus and SpringerLink identified 1,442 records; 27 studies met the eligibility criteria. Study characteristics were extracted using a structured form and synthesized through descriptive frequency analysis and qualitative thematic synthesis. Effectiveness was determined from the direction and consistency of statistically supported quantitative findings and analytically supported qualitative findings rather than from the frequency of outcome variables alone. The evidence shows that quantitative designs were most common (40.74%), studies were concentrated in Turkey, China, and Indonesia, and 92.59% were conducted at elementary or secondary levels. Regular classrooms accounted for 62.96% of implementation contexts. Student products were dominated by engineering structures, robotics and automated systems, and energy-related devices. Cognitive outcomes, especially higher-order thinking skills, were assessed most frequently, while affective and performance outcomes received less attention. Across heterogeneous designs, STEM-EDP produced predominantly positive findings for problem-solving, critical and creative thinking, engagement, self-efficacy, engineering design, collaboration, and product performance. However, short-term classroom interventions and limited higher-education and cocurricular evidence constrain generalization. These results provide a context-process-product-outcome map for designing and evaluating STEM-EDP physics learning.